Rest-activity rhythm disturbance in liver cirrhosis and association with cognitive impairment. Issue 6 (25th December 2020) - Kim, Minjee; Liotta, Eric M; Maas, Matthew B; Braun, Rosemary I; Garcia-Canga, Blas; Ganger, Daniel R; Ladner, Daniela P; Reid, Kathryn J; Zee, Phyllis C
Abstract: Cognitive impairment and disturbed sleep–wake rhythms are disabling complications of liver cirrhosis, yet there is limited understanding of how they are related. We tested the hypothesis that alterations of sleep, rest-activity, and light exposure patterns are associated with worse cognition in cirrhosis. A total of 54 ambulatory adult patients with cirrhosis and 41 age-/gender-matched healthy controls wore wrist actigraphy for rest-activity and light measurements and completed Patient-Reported Outcomes Measurement Information System sleep instruments for self-reported sleep quality. We used standard nonparametric descriptors to characterize rest-activity and light patterns, and wake after sleep onset and sleep efficiency to assess objective sleep quality. The NIH Toolbox cognition battery was used for objective cognitive evaluation using T-scores from a demographically adjusted population reference. Spearman's correlation and multivariable models were used to explore associations between measures of cognition, sleep, rest-activity, and light. Cognition was significantly impaired in cirrhosis patients. Sleep quality was worse in cirrhosis patients by subjective and objective measures compared with controls. Cirrhosis patients exhibited fragmented and dampened rest-activity rhythms, lower daytime and higher nighttime light exposure compared with controls. Worse working memory and processing speed was associated with lower daytime activity level, higher rest-activity fragmentation, lower day-to-day stability, and greater nocturnal light exposure. No association was found between cognition and sleep quality. Rest-activity fragmentation and abnormal light exposure patterns are common in patients with liver disease and are associated with the severity of cognitive impairment. Further research is needed to investigate the effects of timed bright light and exercise intervention on cognitive function in patients with liver disease.